Leaf application of a sprayable bioplastic‐based formulation of biocontrol Aspergillus flavus strains for reduction of aflatoxins in corn. Issue 8 (8th December 2015) - Accinelli, Cesare; Abbas, Hamed K; Vicari, Alberto; Shier, W Thomas
Abstract: BACKGROUND: Applying non‐aflatoxin‐producing Aspergillus flavus isolates to the soil has been shown to be effective in reducing aflatoxin levels in harvested crops, including peanuts, cotton and corn. The aim of this study was to evaluate the possibility of controlling aflatoxin contamination using a novel sprayable formulation consisting of a partially gelatinized starch‐based bioplastic dispersion embedded with spores of biocontrol A. flavus strains, which is applied to the leaf surfaces of corn plants. RESULTS: The formulation was shown to be adherent, resulting in colonization of leaf surfaces with the biocontrol strain of A. flavus, and to reduce aflatoxin contamination of harvested kernels by up to 80% in Northern Italy and by up to 89% in the Mississippi Delta. The percentage of aflatoxin‐producing isolates in the soil reservoir under leaf‐treated corn was not significantly changed, even when the soil was amended with additional A. flavus as a model of changes to the soil reservoir that occur in no‐till agriculture. CONCLUSIONS: This study indicated that it is not necessary to treat the soil reservoir in order to achieve effective biocontrol of aflatoxin contamination in kernel corn. Spraying this novel bioplastic‐based formulation to leaves can be an effective alternative in the biocontrol of A. flavus in corn. © 2015 Society of Chemical Industry